Global change across the Oligocene‐Miocene transition: High‐resolution stable isotope records from IODP Site U1334 (equatorial Pacific Ocean). (16th January 2016) - Beddow, Helen M.; Liebrand, Diederik; Sluijs, Appy; Wade, Bridget S.; Lourens, Lucas J.
Abstract: The Oligocene‐Miocene transition (OMT) ( 23 Ma) is interpreted as a transient global cooling event, associated with a large‐scale Antarctic ice sheet expansion. Here we present a 2.23 Myr long high‐resolution ( 3 kyr) benthic foraminiferal oxygen and carbon isotope (δ 18 O and δ 13 C) record from Integrated Ocean Drilling Program Site U1334 (eastern equatorial Pacific Ocean), covering the interval from 21.91 to 24.14 Ma. To date, five other high‐resolution benthic foraminiferal stable isotope stratigraphies across this time interval have been published, showing a 1‰ increase in benthic foraminiferal δ 18 O across the OMT. However, these records are still few and spatially limited and no clear understanding exists of the global versus local imprints. We show that trends and the amplitudes of change are similar at Site U1334 as in other high‐resolution stable isotope records, suggesting that these represent global deep water signals. We create a benthic foraminiferal stable isotope stack across the OMT by combining Site U1334 with records from ODP Sites 926, 929, 1090, 1264, and 1218 to best approximate the global signal. We find that isotopic gradients between sites indicate interbasinal and intrabasinal variabilities in deep water masses and, in particular, note an offset between the equatorial Atlantic and the equatorial Pacific, suggesting that a distinct temperature gradient was present during the OMT between these deep water masses at low latitudes. A convergence in the δ 18 O values between infaunal and epifaunal species occurs between 22.8 and 23.2 Ma, associated with the maximum δ 18 O excursion at the OMT, suggesting climatic changes associated with the OMT had an effect on interspecies offsets of benthic foraminifera. Our data indicate a maximum glacioeustatic sea level change of 50 m across the OMT. Key Points: A new high‐resolution record of the OMT from Site U1334 Site U1334 stable isotope data represent global deep water signals We create a benthic foraminiferal stable isotope stack across the OMT